2014
DOI: 10.1186/s40608-014-0017-1
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual classification of parents’ attributions of the role of food advertising in children’s diets

Abstract: Background: High levels of child obesity are triggering growing concerns about the prevalence and effects of food advertising targeted at children. Efforts to address this advertising are confounded by the expanding repertoire of media and promotional techniques used to reach and attract children. The present study explored parents' views on food marketing and the strategies parents employ when attempting to ameliorate its effects. As part of an online survey of Australian parents' attitudes towards a range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
0
6
0
1
Order By: Relevance
“…Food marketing is known to stimulate children's purchase requests (Story & French, 2004), and previous studies have found that parents readily attribute at least some of their children's pestering behaviours to the very high prevalence of advertising for unhealthy products (Harris, Fleming Milici, Sarda, & Schwartz, 2012;Kelly, Chapman, Hardy, King, & Farrell, 2009;Mehta, Coveney, Ward, & Handsley, 2014;Pettigrew, Chapman, Miller, & Thomas, 2014). As such, efforts to reduce child pestering for soft drinks are needed to address the pervasive marketing of soft drinks in Australia .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Food marketing is known to stimulate children's purchase requests (Story & French, 2004), and previous studies have found that parents readily attribute at least some of their children's pestering behaviours to the very high prevalence of advertising for unhealthy products (Harris, Fleming Milici, Sarda, & Schwartz, 2012;Kelly, Chapman, Hardy, King, & Farrell, 2009;Mehta, Coveney, Ward, & Handsley, 2014;Pettigrew, Chapman, Miller, & Thomas, 2014). As such, efforts to reduce child pestering for soft drinks are needed to address the pervasive marketing of soft drinks in Australia .…”
Section: Discussionmentioning
confidence: 95%
“…Research suggests that exposure to food marketing makes parents' attitudes more positive and increases the likelihood that the products will be purchased for children (Dixon et al, 2011;Grier, Mensinger, Huang, Kumanyika, & Stettler, 2007). Along with more effective advertising regulation, another, albeit more costly, strategy is to invest in counter messages that promote healthy diets and inform both parents and children of the tactics employed by those seeking to increase sales of unhealthy foods and beverages (Dixon et al, 2014;Pettigrew et al, 2014). The results of the present study relating to the effect of weekend television viewing on attitudes to soft drinks suggest that counter messages are likely to have the most positive impact if disseminated primarily at weekends.…”
Section: Discussionmentioning
confidence: 99%
“…Research has indicated that although parents accept their responsibility to guide their children's food choices [35][36][37][38][39], they may feel undermined or disempowered by unhealthy food marketing [36,[40][41][42][43][44] and support stricter regulatory policies to support them [35,39,40,43,[45][46][47][48][49][50]. In studies spanning Australia, US, Pakistan, India, UK, Ireland and Indonesia, parents consistently reported feeling concerned about children's exposure to unhealthy food marketing [36,[39][40][41][42][43][50][51][52].…”
Section: Extent Of Parental Concern About Children's Exposure To Unhe...mentioning
confidence: 99%
“…In an Australian study in 2014 [49], 235 Australian parents responded to an open-ended online survey question about their attitudes towards food advertising and children's diets. Overall, 78% of respondents perceived unhealthy food advertising to have a negative impact on children's diets.…”
Section: Extent Of Parental Concern About Children's Exposure To Unhe...mentioning
confidence: 99%
See 1 more Smart Citation